2009
DOI: 10.1002/eji.200838710
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell‐specific deletion of gp130 renders the highly susceptible IL‐10‐deficient mouse resistant to intestinal nematode infection

Abstract: Gp130 is the common receptor of the IL-6 family of cytokines and is involved in many biological processes, including acute phase response, inflammation and immune reactions. To investigate the role of gp130 under inflammatory conditions, T-cell-specific conditional gp130 mice were first bred to the IL-10-deficient background and were then infected with the gastrointestinal nematode Trichuris muris. While IL-10 À/À mice were highly susceptible to T. muris, developed a mixed Th1/Th17 response and displayed sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…In contrast to immuno-suppressive effects of IL-10, IL-6 signaling on T cells has been suggested to be critical for mediating as well as sustaining enteric inflammation (Fasnacht et al, 2009). To identify if IL-6 signaling plays a similar role in Treg cells, we examined Foxp3 Cre Il6ra fl/fl mice.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to immuno-suppressive effects of IL-10, IL-6 signaling on T cells has been suggested to be critical for mediating as well as sustaining enteric inflammation (Fasnacht et al, 2009). To identify if IL-6 signaling plays a similar role in Treg cells, we examined Foxp3 Cre Il6ra fl/fl mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, flow cytometric analysis of IgG 2a/c expression on B cells revealed a profound reduction in the proportion of isotype-switched IgD − IgM − B cells that were IgG 2a/c + in the absence of T cell specific gp130 at day 12 after ARM infection (Figure 3c). Skewing of antibody responses from IgG 2a toward IgG 1 has commonly been associated with increased Th2 immunity, and gp130 signaling has previously been reported to enhance Th2 to immune responses (27). However, we found that after LCMV ARM infection the expression of Gata3 , the canonical transcription factor associated with Th2 differentiation, was not significantly altered in FACS isolated T EFF , T FH and virus specific (I-A b GP 67–77 + ) CD4 + T cells in the absence of gp130 (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that T cell specific deletion of gp130 during infection with gastrointestinal nematode Trichuris muris strongly polarizes the immune responses away from pathogenic Th1/Th17 responses towards protective Th2 responses (27). In the strongly Th1 environment of LCMV ARM infection we found little evidence of increased Th2 cell differentiation in the absence of gp130.…”
Section: Introductionmentioning
confidence: 99%
“…The DEREG studies suggest that they are not, or at least that compensatory populations can come in and function in their absence. The CD4 + T cell does appear to be the critical source required for controlling intestinal pathology, however (192). In terms of IL-10 control of pathology, chronic T. muris infection is associated with upregulation of IL-10R and SOCS3 in addition to IL-10 and IFN-γ in the intestine (126,193).…”
Section: Mechanisms Of Host Regulationmentioning
confidence: 96%